2002
DOI: 10.1097/00005537-200202000-00026
|View full text |Cite
|
Sign up to set email alerts
|

A New Paramedian Approach to Arytenoid Adduction and Strap Muscle Transposition for Vocal Fold Medialization

Abstract: The results suggest that a paramedian approach to arytenoid adduction combined with strap muscle transposition is a safe and effective method for treating glottal incompetence, particularly in patients with unilateral paralytic dysphonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…haematoma requiring tracheostomy) to range from 0 to 10 per cent. 5,21,22 In the present study, the incidence of serious complications did not exceed this range. Four patients developed mild post-operative complications, while one developed stridor and shortness of breath necessitating a tracheotomy.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…haematoma requiring tracheostomy) to range from 0 to 10 per cent. 5,21,22 In the present study, the incidence of serious complications did not exceed this range. Four patients developed mild post-operative complications, while one developed stridor and shortness of breath necessitating a tracheotomy.…”
Section: Discussionsupporting
confidence: 40%
“…5,21,22 Some investigators have reported the incidence of severe complications (e.g. haematoma requiring tracheostomy) to range from 0 to 10 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, transposition of the right sternohyoid muscle to the paraglottic space was performed 11 months after endoscopic laser thyroarytenoid myoneurectomy, according to Su et al 24 and improved glottic closure. After this second procedure, the patient remained with mild breathiness, and no recurrence of spasms was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Even in this situation, the patient referred voice quality improvement as compared with the preoperative condition. The glottal gap was corrected surgically with transposition of the strap muscles to the paraglottic space, 24 leading to an overall improvement of voice after both surgical procedures (VHI change ¼ 78 points and subjective voice improvement ¼ 90%). No voice spasm relapse was observed after the second procedure.…”
Section: E10mentioning
confidence: 99%
“…[3][4][5][6][7] In the 1970s, Isshiki et al's work yielded a systematic approach to laryngeal framework surgery [8][9][10] ; his thyroplasty type I and arytenoid adduction techniques became the foundation for laryngeal framework surgery on which several others have based their innovations. [11][12][13][14][15][16][17][18][19][20][21][22][23] Silastic implants can be custom-carved for medialization thyroplasty as described by 24,25 ; or, prefashioned silastic implant systems can be used as described by Montgomery et al 15,17 The use of GORE-TEX (W.L. Gore and Associates, Flagstaff, AZ) for medialization was first described by Hoffman and McCulloch in 1996.…”
Section: Introductionmentioning
confidence: 99%